1986
DOI: 10.1021/j100412a109
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between molecular reorientation dynamics of ionic probes in polar fluids and dielectric friction by picosecond modulation spectroscopy

Abstract: done with the system 0.03 m CTAB + 0.04 and 0.08 m K(Br:Cl). The results for R(90) and Z)app are plotted against the bromide molar fraction XBr in Figure 10, a and b. At 0.04 m both systems have small aggregates and the difference in all properties is small and monotonic from = 0 to 1. At 0.08 m K(Br:Cl), J?(90) and Z>app are almost constant up to XBr = 0.6. At higher bromide content the growth is reflected in both properties. The parameter µ2/ 21 2 is related to the polydispersity of the system.17 It has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…They studied the rotational diffusion of these solutes in alcohols, amides, DMSO and water-alcohol binary systems by pumpprobe polarisation anisotropy. 20,21 They observed that the rotational times in the alcohols are much longer than for the other solvents, similar to our case. Following the MK treatment of the dielectric friction coefficient they derived the following expression of the correlation time where and D r is the rotational diffusion constant (11) (12) (13) (14) We have used these equations, the NZ theory ([eq.…”
Section: Dielectric Frictionsupporting
confidence: 89%
See 2 more Smart Citations
“…They studied the rotational diffusion of these solutes in alcohols, amides, DMSO and water-alcohol binary systems by pumpprobe polarisation anisotropy. 20,21 They observed that the rotational times in the alcohols are much longer than for the other solvents, similar to our case. Following the MK treatment of the dielectric friction coefficient they derived the following expression of the correlation time where and D r is the rotational diffusion constant (11) (12) (13) (14) We have used these equations, the NZ theory ([eq.…”
Section: Dielectric Frictionsupporting
confidence: 89%
“…The two pioneering works of Eisenthal and coworkers 1,2 have triggered off a large number of similar studies of picosecond depolarisation of either the absorbance or the fluorescence of various dye molecules in different solvents, many testing more or less directly the validity of a linear τ R = f(η/T) dependency, either only within the "stick" limit, [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] or considering also the "slip" limit. [28][29][30][31] Interestingly, most papers have reported qualitative accordance with the prediction of a linear η/Tdependency, but only when varying η for a restricted class of solvents (protic, aprotic, n-alcohols, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,11,35 Recent investigations, however, attributed the observed slower reorientation times to electrical aspects of the solute-solvent coupling known as the dielectric friction. The rotational dynamics of a number of polar solutes in polar solvents have been studied to stress the importance of dielectric friction [15][16][17][18][19][20][21][22][23][24][25][32][33][34][35][36] and also to test various theories of dielectric friction. [26][27][28][29][30][31] Since almost all the probe molecules used in these investigations have functional groups like CvO, NH, and NH 2 , chemical intuition tells us that these groups form hydrogen bonds with protic and aprotic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…5,28 -35 These theories have been carefully compared to experimental data [36][37][38][39][40][41][42][43][44][45][46] as well as with molecular dynamics ͑MD͒ simulations. 6,47-50 Although quantitative agreement between theory and experiment has not always been Rotational correlation times, R , reduced correlation times, R /, and initial anisotropy values, r 0 , obtained from fits of polarized fluorescence decays.…”
Section: A Backgroundmentioning
confidence: 99%